Proteomic Analysis Revealed Underlying Biological Pathways Associated with Hormetic Response of Hormone Positive Breast Cancer Cell Line Exposed to Low-Dose Flavonoid Mixture - Mete Bora Tüzüner; Ayşe Begüm Ceviz (European Journal of Biology)
Objective: A considerable level of evidence has accumulated about the breast cancer risk-reducing effect of consuming specific flavonoids, through the increasing amount of research and epidemiologic studies. Different flavonoids may have different cellular bioavailability and favor, i.e., the occurrence of a hormetic effect, thus it is important to evaluate breast cancer cells’ response to different doses of flavonoids. This study aims to investigate the alterations of the biological pathways in a hormone-positive (HR+) breast cancer cell line as a resemblance for the most common breast cancer subtype, related to the low-dose exposure of the flavonoids. Materials and Methods: Different levels of doses were applied to MCF-7 breast cancer cells. In order to determine cellular proliferation, WST-1 analysis was conducted. The highest proliferation was observed with cell lines exposed to a low-dose flavonoid mixture and these were selected for further analysis. Intracellular protein expression were investigated by peptide analysis on a nano LC-MS/MS platform. A protein-protein interaction network and pathway analysis were conducted for the proteins expressed differently between the groups. Results: A total of 214 proteins were identified and 36 proteins with significant alterations (≥1.2-fold change, p≤0.05) were detected. Significant changes were observed in the pathways related to carbon metabolism, amino acid biosynthesis, splicing mechanism, mitochondrial protein import and translation elongation pathways. Conclusion: Our study demonstrated that flavonoids can have a hormetic effect which can initially alter metabolic pathways vital for cell proliferation and survival. These pathways may include potential targets for enhancing the anticancer activity of the flavonoids.